As you like it. - Milton, Robert, 1885-1956.; Simonson, Lee, 1888-1967.; Bendix, Theo. (Theodore); Shakespeare, William, 1564-1616.; Poli's Theatre (Washington, D.C.); Theater Playbills and Programs Collection (Library of Congress) (1923)
Poli's Theatre, S.Z. Poli, proprietor, presenting Shubert attractions, the American National Theatrer presents William Shakespeare's "As You Like It," produced by Robert Milton, production designed by Lee Simonson. The incidental music composed and arranged by Theo. Bendix. Theo. Bendix, conductor.
Program of entre-act music: Overture "As You Like It" / Tobani-Bendix -- Idyle "In Beauty's Bower" / Bendix -- The Bee / Bendix -- Woodland sketches / Howgill -- Mock Morris / Grainger -- Suite " In the Forest" / Nicode -- Gavotte / Gossac -- Selections from "Merrie England" German triumphant march -- The Duke's Return / Bendix.
Poli's Theatre [Washington, D.C.], week of Monday, April 16, 1923, matinees Thursday and Saturday.
Title devised by Library staff.
Cast: Albert Powers, Ian Keith, Arnold Lucy, Jerome Lawlor, Hall Higley, Stanley Kalkhurst, Edna Rivers, Dorothy Chase, Hilda Dallmann, Adele Schuyler, Marjorie Rambeau, Margalo Gillmore, Ernest Lawford, Edgar Norton, John Craig, Frank Arundel, A.E. Anson, J. Malcom Dunn, Walter Abel, William Williams, Hortense Alden, Gwynedd Vernon, Percival Vivian, G. Anderson, Norton Meyers, Mercedes de Cordoba. Ladies of the court: Maria NaMara, Olga Brent, Isabel Garland, Ann Tonetti, Betty Watson, Anita Inglis. Guardsmen: Charney Batson, Lynn Berry, H. Berbert, Earl Marvin, James Sumner, Ben Webster. Lords at court: John Navarre, Albert Cummings, Theodore Ranstead, Oscar Johnson, Antony Carr, A.H. Hill. Lords in the forest: G. Albert Smith, Gregory Safronic, William Fliedner, George Kendall, Frank Pierce, Richard Mason. Foresters: Jay Fasset, Alvin Eley, Norman Jones, Carl Parsons, Donald Davis, Charles Masters. Shepherdesses: Josephine Meyers, Florence Anderson, Lucy Ditmara, Evelyn Pope, Alice Tombs, Helen Knox, Vera Townsend, Emma Livingston, Gertrude Bright, Viola Stutton.
"Next week ... A. H. Woods presents ... Paulline Frederick ... in ... 'The Guilty One' by Michael Morton and Peter Trail".
In: American theater programs of the late 19th and 20th centuries (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1904.